2007
DOI: 10.1002/ajh.20854
|View full text |Cite
|
Sign up to set email alerts
|

Florid histiocytic hemophagocytosis following therapy with long acting G‐CSF (pegfilgrastim)

Abstract: We describe a case of histiocytic hemophagocytosis and increase in blasts in the bone marrow after administration of long acting G-CSF (pegfilgrastim) in a 71-year-old man with underlying myelodysplasia. Pegfilgrastim was discontinued, with resolution of the hemophagocytosis and marked decrease in blasts from 30 to 5%. We postulate that pegfilgrastim provided a continuous stimulation of the monocyte/macrophage system, resulting in histiocytic hemophagocytosis. We recommend caution in defining indications for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…There are 2 major possibilities as to how IFNγ regulates the expression of GM‐CSF: either GM‐CSF production by CD8+ T cells is a default state in the absence of IFNγ signaling, or other compensatory signaling pathways that promote GM‐CSF production are up‐regulated in the absence of IFNγ. Interestingly, there have been case reports of patients who, while receiving myeloablative chemotherapy, had been administered recombinant GM‐CSF or the related granulocyte colony‐stimulating factor and developed HLH , suggesting a possible causative role of myeloid‐specifying cytokines in the pathogenesis of some subsets of HLH patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are 2 major possibilities as to how IFNγ regulates the expression of GM‐CSF: either GM‐CSF production by CD8+ T cells is a default state in the absence of IFNγ signaling, or other compensatory signaling pathways that promote GM‐CSF production are up‐regulated in the absence of IFNγ. Interestingly, there have been case reports of patients who, while receiving myeloablative chemotherapy, had been administered recombinant GM‐CSF or the related granulocyte colony‐stimulating factor and developed HLH , suggesting a possible causative role of myeloid‐specifying cytokines in the pathogenesis of some subsets of HLH patients.…”
Section: Discussionmentioning
confidence: 99%
“…27 G-CSF is postulated to interact with G-CSF receptors on monocytes, providing continuous stimulation with pharmacological rather than lower physiological concentrations of growth factor. 28 A feedback Emerging evidence suggests a role for GM-CSF in HLH, based on admin istration of recombinant G-CSF in patients with this disorder. In clinical practice, there are concerns that administration of G-CSF might worsen HLH; indeed, the observation that administration of recombinant G-CSF (eg, lenograstim) exacerbated syno vitis supported the rationale to target the GM-CSF pathway in rheumatoid arthritis.…”
Section: Gm-csf and Neutrophils In Hyperinflammationmentioning
confidence: 99%
“…The subsequent onset of florid HLH was temporally related to G‐CSF, raising the possibility that cytokine stimulation was an exacerbating event. Several case reports suggest that G‐CSF can trigger florid HLH in patients with haematological malignancies, but unlike the current study none of the reported cases were analysed for FHL‐related genes 17–20 . The mechanism by which this occurs is unknown; however, it is plausible that G‐CSF further stimulated activated macrophages through the G‐CSF receptor, leading to hyperactivation and hypersecretion and a self‐perpetuating cycle of inflammation which persisted in the absence of supraphysiological stimulus.…”
Section: Discussionmentioning
confidence: 67%